PROFIL KEMAMPUAN BERPIKIR KREATIF SISWA KELAS VIII DALAM MEMECAHKAN MASALAH MATEMATIKA SOAL MODEL PISA FOKUS KONTEN QUANTITY BERDASARKAN KEARIFAN LOKAL - Setiawan, Toto Bara; Dafik, Dafik; Laili, Nuryatul (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research aims to describe students creative thinking skill of VIII grade SMP Negeri 4 Jember in solving mathematical problem using local wisdom PISA test of quantity content. The local wisdom used in this research comes from Jember regency, namely “petik laut” and “sangkar burung” in Dawuhan village. The subject is choosen from class VIII G based on the students' mathematical skill which is taken from the UTS score that has been obtained. The classification shows that there are 7 students with the high score, 23 students in the middle level, and 6 students get the low score. The research subjects consist of 2 students in each category of mathematical skill. Data analysis is done based on problem-solving tests and interviewing tests. The students with high math skills are able to achieve 2 key components of creative thinking, namely, fluency, and flexibility. The students with the middle level of math skills are able to achieve 1 key component of creative thinking, namely, fluency. The students with low math skills are unable to achieve the three key components of creative thinking: fluency, flexibility, and novelty. Keywords: Creative Thinking, Math Skill , Local Wisdom